The present state of system analysis and design in East Malaysia - Syed Nasirin Syed Zainol Abidin; Esmadi Abu Abu Seman; H. Ismail; Iza Azura Ahmad Bahar; Jackel, Chew Vui Lung; Nooralisa Mohd Tuah; Abdullah Mohd. Tahir; Suddin Lada (Springer, Cham, 2021)
Many government agencies everywhere in the globe, including those in the developing regions, are intimately involved in developing their Information Systems (IS) projects. To favourably develop these IS projects, those agencies have spent lots of funding, forces and time to assure that they are amply equipped with the latest system design and analysis methods. However, the literature is scarce with the published evidence showing that these government agencies are claiming that they have successfully used these cultivated analysis and design techniques. The intricate system analysis and design techniques may only remain theoretical with limited use. Many of these system analysis and design techniques had never succeeded the claimed benefits made when they were acquired, which begs the principal research question of what is the present deployment state of system analysis and design in these government institutions, particularly in the developing regions? The article thus discusses the exploratory case studies on the present state of system analysis and design methods deployed by the public institutions in East Malaysia, a developing region within South-East Asia.